Sustainable Interdisciplinarity: Human-Nature Relations - Cirella, Giuseppe (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Sustainable interdisciplinarity focuses on human-nature relations and a multitude of contemporary overlapping research between society and the environment. A variety of disciplines have played a large part in better understanding sustainable development since its high-profile emergence approximately a quarter of a century ago. At present, the forefront of sustainability research is an array of methods, techniques, and growing knowledge base that considers past, present, and future pathways. Specific multidisciplinary concentrations within the scope of societal changes, urban landscape transformations, international environmental comparative studies, as well as key theories and dynamics relating to sustainable performance are explored. Specializations in complex sustainability issues address international governance arrangements, rules, and organizations-both public and private-within the scope of four themes: sustainability, human geography, environment, and interdisciplinary societal studies. This book contains eleven thoroughly refereed contributions concerning pressing issues that interlink sustainable interdisciplinarity with the presented themes in terms of the human-nature interface.